2015
DOI: 10.1002/cjce.22342
|View full text |Cite
|
Sign up to set email alerts
|

Free fall and controlled gravity drainage processes in fractured porous media: Laboratory and modelling investigation

Abstract: Gravity drainage is known to be one of the most effective methods for oil recovery in fractured reservoirs. In this study, both free fall and controlled gravity drainage processes were studied using a transparent fractured experimental model, followed by modelling using commercial CFD software. The governing equations were employed based on the Darcy and mass conservation laws and partial pressure formulation. Comprehensive examination was done on variables such as fluid saturation, velocity, and pressure dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Major results reported by researchers in this field could be classified into two general categories: first, increasing the model height and decreasing capillary pressure improve the process efficiency; second, the presence of a driving viscous force leads to earlier breakthrough and can improve the ultimate recovery factor (i.e., forced gravity drainage). Notably, lower recovery factor by increasing the gas injection rate is also reported after a critical gas injection rate (Rostami et al 2010;Akhlaghi et al 2012;Saedi et al 2015;Zobeidi et al 2016). Firoozabadi and Markeset (1992) and Firoozabadi and Markeset (1994) used spacers of different thicknesses (up to 1.2 mm) as horizontal fractures in a multi-stack block system.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Major results reported by researchers in this field could be classified into two general categories: first, increasing the model height and decreasing capillary pressure improve the process efficiency; second, the presence of a driving viscous force leads to earlier breakthrough and can improve the ultimate recovery factor (i.e., forced gravity drainage). Notably, lower recovery factor by increasing the gas injection rate is also reported after a critical gas injection rate (Rostami et al 2010;Akhlaghi et al 2012;Saedi et al 2015;Zobeidi et al 2016). Firoozabadi and Markeset (1992) and Firoozabadi and Markeset (1994) used spacers of different thicknesses (up to 1.2 mm) as horizontal fractures in a multi-stack block system.…”
Section: Introductionmentioning
confidence: 88%
“…Numerous experimental studies have been conducted on the gravity drainage mechanisms. The majority of these studies were performed on synthetic porous media such as coarse quartz grains sand packs with high permeability, so that the duration of each experiment, as well as the set-up height, can be adequately decreased (Moon and Bruce 2007;Zendehboudi et al 2011;Saedi et al 2015;Teng et al 2016). Saidi et al (1979) studied the interaction of matrix blocks and the presence of capillary continuity and reinfiltration between adjacent matrix blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…r Preparing or editing figures [46] r Supplying samples [47] r Supplying data r Writing programs [38] r Discussing the results [48] r Editing and proofreading [40,36] r Access to departmental facilities [49] …”
Section: Other Types Of Acknowledgementsmentioning
confidence: 99%
“…Some studies have investigated the effects of wettability in fractured and homogeneous porous media during free-fall gravity drainage (FFGD) and controlled gravity drainage (CGD) conditions (Zendehboudi et al, 2011;Zendehboudi et al, 2012;Maroufi et al, 2013;Saedi et al, 2015). These studies have shown that different wettability conditions govern the oil recovery mechanism during FFGD and CGD processes.…”
Section: Fractured Reservoirsmentioning
confidence: 99%